Bibliometric Analysis of Research Development of Smart Learning Environment for Education in Indonesia - Nuril amini (Universitas Negeri Malang, 2023)
Smart Learning environment has great potential to emphasizes learning flexibility, effectiveness,efficiency, engagement, adaptavity, and reflectiveness. So it is important to map the research thathas been done so that it become strategy to explore its use for efficient development. To determinearticle content, authorship pattern, and productivity of educational writers, a bibliometric studywas conducted. The data sources is the google scholar indexer, this smart learning environmentarticle in indonesia is spread in various journals. In general, during 2010-2023 period as many as126 resecarchers produced 50 articles, the fields that most often appeared were those related tolearning and education, the most latest trend of article related to evelopment of a learningmanagement system as a smart learning environmet on improving student cognitive, litercy skilland student’s readiness for self-regulated learners. the most published research publications inafter 2016 namely 44 articles (88%). And most of the, them related to concept of SLE, design andpractical insight into online learning resources. And there are only 14 articles (0,28%) outside thetheme of learning and education, namely 2 articles (0,04%) related to communication published inwireless personal communication, so are 2 article (0,04%) related to computer science andemerging technology, and namely 1 article (0,02%) related to machine learning, cloud computing,IOT, AI, city governance published on various journal.